Methylation of slipped duplexes, snapbacks and cruciforms by human DNA(cytosine-5)methyltransferase. - Laayoun, A (1995)
When human DNA(cytosine-5)methyltransferase was used to methylate a series of snapback oligodeoxy-nucleotides of differing stem lengths, each containing a centrally located CG dinucleotide recognition site, the enzyme required a minimum of 22 base pairs in the stem for maximum activity. Extrahelical cytosines in slipped duplexes that were 30 base pairs in length acted as effective methyl acceptors and were more rapidly methylated than cytosines that were Watson-Crick paired. Duplexes containing hairpins of CCG repeats in cruciform structures in which the enzyme recognition sequence was disrupted by a C.C mispair were also more rapidly methylated than control Watson-Crick-paired duplexes. Since enzymes have higher affinities for their transition states than for their substrates, the results with extrahelical and mispaired cytosines suggest that these structures can be viewed as analogs of the transition state intermediates produced during catalysis by methyltransferases.